Use of Denaturing High-Performance Liquid Chromatography To Identify Bacillus anthracis by Analysis of the 16S-23S rRNA Interspacer Region and gyrA Gene - Hurtle, William (American Society for Microbiology, 2003)
Denaturing high-performance liquid chromatography (DHPLC) was evaluated as a method for identifying Bacillus anthracis by analyzing two chromosomal targets, the 16S-23S intergenic spacer region (ISR) and the gyrA gene. The 16S-23S ISR was analyzed by this method with 42 strains of B. anthracis, 36 strains of Bacillus cereus, and 12 strains of Bacillus thuringiensis; the gyrA gene was analyzed by this method with 33 strains of B. anthracis, 27 strains of B. cereus, and 9 strains of B. thuringiensis. Two blind panels of 45 samples each were analyzed to evaluate the potential diagnostic capability of this method. Our results show that DHPLC is an efficient method for the identification of B. anthracis.